Kinetic characterization of red pigment of Monascus purpureus at different level of nitrogen concentration - Siti Mahira, Ahmad; Farhan, Mohd Said (Science Publishing Corporation Inc, 2018)
Natural and synthetics colors are the two types of food coloring existed in the industries. Over time, most of synthetic colors were banned due to the clearly evident side effects and their possible carcinogenic effects. Pigment produced by Monascus purpureus is microbial origin and safe to use as food grade coloring. The aim of this research is to study the kinetic characterization of red pigment production throughout the solid state fermentation process at different level of nitrogen (peptone) concentration. The concentrations of nitrogen used are in between 1 to 5% of peptone. The highest μmax (0.1182 day-1), P cells (119.7 g ml-1 day-1), YX/S (1.35), YP/S (1.35), and YP/X (0.016) are obtained at day 5 of fermentation period with the addition of 2% peptone. However, no further increase of the kinetic values with the increasing of peptone concentration from 2% to 5% was observed, except on YP/X where the value was high with higher concentration. This indicates that with higher concentration the conversion of biomass to red pigment is enhanced.